2020
DOI: 10.1111/ijsa.12304
|View full text |Cite
|
Sign up to set email alerts
|

How protestant work ethic impacts employees' counterproductive work behaviors: The moderating effects of gender and party affiliation

Abstract: This study examined the relationships between the four dimensions of the protestant work ethic (internal locus of control, asceticism, hard work, anti‐leisure) and organizational counterproductive work behaviors (CWBs). Based on a sample of Chinese employees, the results from two‐wave lagged data (N = 691) indicated that the asceticism dimension and the anti‐leisure dimension were negatively associated with CWBs. These associations were moderated by party affiliation, indicating that party members had a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Indeed there is evidence that perceptions of individuals' industriousness is used as a heuristic to inform moral attributions (Amos et al, 2019). Interest in PWE has been associated with belief that it is associated with productivity (Mudrack, 1999;Zhang, 2020) although evidence for a link between PWE and economic success is limited (Hoorn, 2013). For example, one argument is that the link between Protestantism and economic prosperity arose due to the promotion of literacy (Becker & Woessmann, 2009).…”
Section: Work Valuesmentioning
confidence: 99%
“…Indeed there is evidence that perceptions of individuals' industriousness is used as a heuristic to inform moral attributions (Amos et al, 2019). Interest in PWE has been associated with belief that it is associated with productivity (Mudrack, 1999;Zhang, 2020) although evidence for a link between PWE and economic success is limited (Hoorn, 2013). For example, one argument is that the link between Protestantism and economic prosperity arose due to the promotion of literacy (Becker & Woessmann, 2009).…”
Section: Work Valuesmentioning
confidence: 99%
“…Alternately, Slabbert and Ukpere (2011) express that productivity can be linked to all the work ethic dimensions with a relationship conditioned by cultural and economic factors of the studied population. Recently, research has found the impact of PWE on counterproductive work behaviors (Zhang et. al., 2020), organizational commitment (Balayodao et al, 2021, and as a positive predictor of unethical pro-organizational behaviors (Grabowski et al, 2021).…”
Section: Jel Codesmentioning
confidence: 99%
“…These are, first, the centrality of work in life, even if one is well off; second, self-reliance, i.e., avoiding dependence on other persons; third, belief in the virtues of hard work; fourth, leisure, i.e., balancing work with valuing the importance of non-work activities; fifth, morality/ethics of fair dealing with others; sixth, delaying gratification, i.e., future orientation; and seven, minimizing wasted time in life. Zhang et al (2020) and Miller et al (2002) construe MWEP as learned not innate; secular, i.e., not tied to any religious beliefs; and motivational in that it instigates work behavior [8,9].…”
Section: Introductionmentioning
confidence: 99%